2018
DOI: 10.2147/cia.s151290
|View full text |Cite
|
Sign up to set email alerts
|

Different doses of steroid injection in elderly patients with carpal tunnel syndrome: a triple-blind, randomized, controlled trial

Abstract: BackgroundCarpal tunnel syndrome (CTS) is commonly seen in elderly populations, in part due to increased presence of predisposing comorbidities as well as physiological changes. We aimed at comparing the effectiveness of different doses of steroid using the ultrasound-guided hydrodissection method in elderly patients with CTS.MethodsWe conducted a prospective, triple-blind, randomized, controlled trial in elderly patients with CTS. Patients were allocated to one of three groups by simplified randomization. Gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
57
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(58 citation statements)
references
References 46 publications
(60 reference statements)
0
57
0
1
Order By: Relevance
“…In the control group, only 1 mL of 2% lidocaine and 2 mL of NS were administered. The authors found no remarkably significant difference between the two groups; then, they concluded that hydrodissection is more important than anti-inflammatory effects of corticosteroids 13. However, because of lidocaine injection in all the groups and other nonspecific benefits of participants for being in an RCT, this effect might not be so “pure”, as the authors have said.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In the control group, only 1 mL of 2% lidocaine and 2 mL of NS were administered. The authors found no remarkably significant difference between the two groups; then, they concluded that hydrodissection is more important than anti-inflammatory effects of corticosteroids 13. However, because of lidocaine injection in all the groups and other nonspecific benefits of participants for being in an RCT, this effect might not be so “pure”, as the authors have said.…”
Section: Discussionmentioning
confidence: 93%
“…Some authors have compared the efficacy and safety of popular corticosteroids at different dosages in CTS patients 1315. O’Gradaigh and Merry compared the outcomes of local injection of long- and short-acting corticosteroids at different dosages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One cadaver study showed decreased gliding resistance of the nerve in the carpal tunnel after hydrodissection (Evers et al, 2018). Two clinical RCTs further showed positive effects of hydrodissection on pain, function and CSA (Roghani et al, 2018;Wu et al, 2019). Our study adopted an identical injection drug (5% dextrose) to eliminate confounding bias of dextrose.…”
Section: Discussionmentioning
confidence: 95%
“…Some of these conservative options are oral medications like non-steroidal anti-inflammatory drugs (NSAIDs), resting wrist splint, physical agent modalities, and local injections including corticosteroid and platelet-rich plasma (PRP) 7–11. Local corticosteroid injection has been approved as one of the most common conservative therapies which are still the best choice for rapid symptom relief 1215. The injection could be performed through multiple approaches.…”
Section: Introductionmentioning
confidence: 99%